The differences of students learning outcome with numbered head together (NHT) and think pair share (TPS) in atomic structure - Feri Andi Syuhada (Jurnal Pendidikan Kimia (JPKim), 2018)
Abstract:       This study determine the differences between student learning outcomes using model of the NHT and TPS type of cooperative teaching on the subject of atomic structure. The population in this study were all grade X at SMA Negeri 1 Percut Sei Tuan. There were 9 classes. The samples were 2 classes with 68 students. The first class was used cooperative teaching model of NHT while the second class was used cooperative teaching model of TPS. The result of the study shows that the application of these two types give influence to the result of student learning outcome in chemistry. The average point of post test for first class is (73.82 + 11.20) and the second class is (77.41 + 10.77).The result is tcount<ttab (-1.34<1.998) with α=0.05, this value conclude that there are no significant differences between student learning outcome by using cooperative teaching model with NHT type and TPS on the subject of atomic structure.Keywords:atomic structure; learning outcome; NHT; TPS